TEORI‐TEORI KELUPAAN - Marnio Pudjono (Faculty of Psychology Universitas Gadjah Mada, 2008)
Forgetting is and has been an important topic in the study of memory. This paper reviewed three theories of forgetting, namely decay theory, transference theory as well as cue‐dependent forgetting theory. Biological bases of forgetting was shortly reviewed as well.